RIVALITAS BONEK DAN AREMANIA DALAM PERSPEKTIF KOMUNIKASI - Ahmad Yusron (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2021)
Supporters are an important part of a football match. It can be said that a supporter is the twelfth player of a football team. The phenomenon of supporters in the world of Indonesian football is the emergence of fanaticism which in the end this fanaticism creates rivalry. This can be seen from the rivalry between Bonek and Aremania. This study aims to find an overview of the rivalry between Bonek and Aremania in perspective communication. The method in this study is a qualitative method with a literature study approach. In this case, the information data is sourced from documentation information, records, and so on.The results obtained in this study are that the support phenomenon is a phenomenon that must occur in the world of football. These supporters have their nicknames. Messages in the rivalry between Persebaya and Arema supporters are dominated by messages that show the hatred of both parties. The second supporting media rivalry generally uses two media, namely conventional media and digital media. The media used to express rivalry have an impact in spreading rivalry between generations and maintaining that rivalry.